2004
DOI: 10.1007/s11906-004-0066-9
|View full text |Cite
|
Sign up to set email alerts
|

Is proteinuria a plausible target of therapy?

Abstract: Microalbuminuria is an independent marker of cardiovascular risk, irrespective of kidney disease. Recent pharmacologic interventions have resulted in a significant delay and even an arrest in the progression of microalbuminuria to macroalbuminuria or to chronic kidney disease. Focus should be placed on agents that not only lower blood pressure but also improve albuminuria levels. Current guidelines recommend that hypertensive patients with renal disease should be started on agents that block the renin-angioten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…Patients with higher baseline proteinuria experienced a relatively faster rate of GFR decline and benefited more from the lower BP goal (1). Numerous analyses have since confirmed this observation (21)(22)(23). Thus, the selection of BP-lowering medications for patients with renal disease should be based on the efficacy of these agents in reducing proteinuria (1).…”
Section: Higher Proteinuria Linked To Faster Decline In Gfrmentioning
confidence: 89%
“…Patients with higher baseline proteinuria experienced a relatively faster rate of GFR decline and benefited more from the lower BP goal (1). Numerous analyses have since confirmed this observation (21)(22)(23). Thus, the selection of BP-lowering medications for patients with renal disease should be based on the efficacy of these agents in reducing proteinuria (1).…”
Section: Higher Proteinuria Linked To Faster Decline In Gfrmentioning
confidence: 89%
“…For example, proteinuria and microalbuminuria are adverse consequences of systemic hypertension in animals with coexistent CKD. With respect to the benefits of decreasing BP in animals with CKD, decreasing the magnitude of proteinuria is perhaps the most effective treatment goal, 161 particularly in cats.…”
Section: The Hypertensive Patient: Follow-upmentioning
confidence: 99%
“…Toyama et al ( 26 ), in a systematic review and meta-analysis of 31 studies, have reported an increased risk of cardiovascular mortality with microalbuminuria [risk ratio (RR), 1.76; 95% CI, 1.38–2.25] and macroalbuminuria (RR, 2.96; 95% CI, 2.44–3.60) as compared to normoalbuminuria in diabetics. Guidelines for the management of hypertension recommend screening as well as targeted management of albuminuria in addition to controlling blood pressure for better clinical outcomes ( 27 ). Despite evidence suggesting the deleterious effects of albuminuria independent of kidney function in patients with other cardiovascular diseases ( 28 , 29 ), there has been limited research on the prognostic significance of this biomarker specifically in heart failure patients.…”
Section: Discussionmentioning
confidence: 99%